Soil potassium as affected by fertilization over the millet straw and simulated rain - Rosolem, Ciro Antonio; Santos, Fernanda Pereira dos; Foloni, José Salvador Simonetti; Calonego, Juliano Carlos (Pesquisa Agropecuaria Brasileira, 2006)
This research aimed to evaluate K leaching through the soil profile, and its presence in the exchangeable and nonexchangeable forms, as affected by simulated rain and potassic fertilizer applied over the pearl millet straw left on soil surface. Pots filled with soil and pearl millet straw (equivalent to 8 t ha-1) in the surface received or not 150 kg ha-1 of K2O, as KCl applied over the straw. Rainfalls from 0 to 50 mm were applied. The soil was analyzed at several depths for exchangeable and nonexchangeable K. Pearl millet straw acts as an important K source, which is leached down to 4 cm depth when subjected to a simulated 30-mm rain. K leaching is positively related to the amount of rain; however, a 50-mm rain does not lead the nutrient down to more than 8 cm depth. The transformation of exchangeable K to non exchangeable K is very fast, as shown by the contents of non exchangeable K in the soil profile down to 4 cm.